OPPORTUNITIES OF USE OF THE BIOFEEDBACK METHOD IN REHABILITATION OF PATIENTS WITH OCCUPATIONAL DISEASES CAUSED BY CHEMICAL AND PHYSICAL FACTORS - P. V. Kazakova; N. G. Sudakova; D. V. Rusanova; E. V. Katamanova; M. P. Dyakovich (Acta Biomedica Scientifica, 2012)
The article shows the opportunity of use of biomonitoring in patients with exogenous toxic encephalopathy in the remote period of chronic mercury intoxication. (CMI) and with, vibration disease caused by local vibration. The efficiency of the biofeedback method was assessed on the basis of the data of electroencephalography, auditory, visual and somatosensoric generated potentials, electroneuromyography, thermometry, dosed cold test and. rheography. Biofeedback training in people with. CMI caused decrease of total brain changes in EEG, improvement of amplitude indices at of the brain generated potentials, in people with vibration disease it caused decrease of manifestation of angiodistonic syndrome and. restoration of neuromuscular conductivity.